Plasma concentrations of CCL3 and CCL4 in the cardiac and digestive clinical forms of chronic Chagas disease - Oliveira, Amanda Priscila de; Ayo, Christiane Maria; Oliveira Mimura, Kallyne Kioko [UNESP]; Oliani, Sonia Maria [UNESP]; Bernardo, Cassia Rubia; Silveira Camargo, Ana Vitoria da; Ronchi, Luis Sergio; Borim, Aldenis Albaneze; Campos Junior, Eumildo de; Brandao de Mattos, Cinara Cassia; Castiglioni, Lilian; Bestetti, Reinaldo Bulgarelli; et al. (Elsevier B.V., 2017)
The aim of this study was to investigate the plasma levels of the CCL3 and CCL4 chemokines in patients with the cardiac and digestive clinical forms of chronic Chagas disease and in cardiac patients with and without left ventricular systolic dysfunction (LVSD). Plasma samples from 75 patients were evaluated by enzyme-linked immunosorbent assay (ELISA) to confirm infection by T. cruzi. Plasma levels of the CCL3 and CCL4 chemokines were measured using Milliplex((R)) MAP assay (Millipore). There were no significant differences in the levels of CCL3 and CCL4 between patients with the digestive and cardiac clinical forms of Chagas disease. Moreover, no significant differences were found between patients without LVSD and those with LVSD. Higher CCL3 and CCL4 plasma levels were found in patients with LVSD compared to those with the digestive form of the disease. The CCL3 and CCL4 chemokines might not be involved in differential susceptibility to the digestive and cardiac clinical forms of chronic Chagas disease, and it seems they do not influence the development of LVSD. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Chagas disease; Chronic Chagas heart disease; CCL3 chemokine; CCL4 chemokine